2014
DOI: 10.1002/icd.1845
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Conflict Links Behavioural Inhibition and Social Problem Solving During Social Exclusion in Childhood

Abstract: Behavioral inhibition (BI) is a temperament characterized by heightened negative affect and social reticence to unfamiliar peers. In a longitudinal study, 291 infants were assessed for BI at 24 and 36 months of age. At age 7, N2 amplitude was measured during a Flanker task. Also at age 7, children experienced social exclusion in the lab during an interaction with an unfamiliar peer and an experimenter. Our findings indicate that children characterized as high in BI, relative to those low in BI, had larger (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
(60 reference statements)
10
22
0
Order By: Relevance
“…For children with a history of BI, smaller ERN amplitudes tended to reduce the probability of a lifetime diagnosis (OR ¼ 0.82, p ¼ 0.06), whereas the ERN was unrelated to probability of diagnosis for children without a history of BI. Importantly, as was the case in the N2/conflict detection studies by Lahat et al (2014b) and Henderson (2010), a history of BI was unrelated to behavioral performance (error rates or reaction times) on the Flanker task, suggesting that the exaggerated cortical responses did not support superior task performance. Examining the association between the ERN and clinically significant anxiety longitudinally, Lahat et al (2014a), in a separate study, reported that BI in toddlerhood was associated with larger ERN amplitudes at 7 years of age.…”
Section: Neural Correlates Of Controlmentioning
confidence: 82%
See 3 more Smart Citations
“…For children with a history of BI, smaller ERN amplitudes tended to reduce the probability of a lifetime diagnosis (OR ¼ 0.82, p ¼ 0.06), whereas the ERN was unrelated to probability of diagnosis for children without a history of BI. Importantly, as was the case in the N2/conflict detection studies by Lahat et al (2014b) and Henderson (2010), a history of BI was unrelated to behavioral performance (error rates or reaction times) on the Flanker task, suggesting that the exaggerated cortical responses did not support superior task performance. Examining the association between the ERN and clinically significant anxiety longitudinally, Lahat et al (2014a), in a separate study, reported that BI in toddlerhood was associated with larger ERN amplitudes at 7 years of age.…”
Section: Neural Correlates Of Controlmentioning
confidence: 82%
“…This is also consistent with the Perez-Edgar et al (2007) finding that adolescents with a history of childhood BI showed exaggerated amygdala responses to all emotion faces (not just threatening ones) when asked to rate their subjective experiences. In addition, it is supported by the finding that enhanced N2 amplitudes on both incompatible (high conflict) and compatible (low conflict) trials linked BI to indices of social and emotional maladaptation (Henderson, 2010;Lahat et al, 2014b) and that a childhood history of BI is associated with the failure to discriminate between positive and negative feedback in vmPFC activation during a monetary incentive delay task in adolescence (Helfinstein et al, 2011).…”
Section: Overgeneralized Control Modelmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies of the relation between N2 magnitude and BI have found that children (7 −8 years of age) characterized by early BI exhibit larger N2 magnitudes during a motor inhibition task (i.e., Go/No-Go Task) compared with less-inhibited children (Lamm et al, 2014). Enhanced N2 activation among behaviorally inhibited children (7 −8 years of age) has also been observed during a stimulus conflict task (Lahat, Walker, et al, 2014). During a dot-probe task, behaviorally inhibited children (7 −8 years of age) exhibit larger N2 amplitude when avoiding threat (Thai, Taber-Thomas, & Perez-Edgar, 2016).…”
Section: Approach-avoidance Conflictmentioning
confidence: 99%